Euphysothrips: an Old World genus of Thripidae (Thysanoptera) associated with rust fungi (Pucciniales) - Mound, Laurence A. (Zootaxa, 2018)
Fungus-feeding is common amongst members of the family Phlaeothripidae that live on dead branches and leaves (Dang et al. 2014). In contrast, associations with fungi are rare amongst the common thrips of the family Thripidae that live in flowers and on leaves. In this family, two species from Africa in the genus Craspedothrips are reported to be associated with the rust fungus, Hemileia vastatrix, on the leaves of coffee plants (Mound et al. 2012), although there are no reports of direct feeding by the thrips on the fungus. However, the two known species of the Asian genus Euphysothrips have been observed to feed on the spores of rust fungi at widely separated localities. One of these, fungivora, was described by Ramakrishna (1928) in the genus Anaphothrips, and he reported this thrips as feeding on “rust” on wheat plants at Coimbatore, India. Ananthakrishnan (1969: 5) subsequently referred to this species as “feeding on the spores of wheat rust, Puccinia graminis”. The second species of Euphysothrips was described by Ramakrishna and Margabandhu (1939) as a new genus and species, Megaphysothrips subramanii, from Mysore in southern India. These authors stated that this thrips was found feeding on coffee rust, and a similar feeding association on coffee was reported from Timor in 1967, when specimens of subramanii were submitted for identification to the Natural History Museum, London. In Timor Leste during August 2018, adults and larvae of subramanii were found commonly on the leaves of coffee plants. The thrips were living only on the reddish-pink patches of Hemileia vastatrix fungus (Fig. 6), and not freely exploring the rest of the leaf surface. Both adults and larvae were difficult to see on these patches of fungus, because each individual was noted to carry a covering of coloured spores. This pinkish covering was shed only when an individual was disturbed by attempts to collect them with a small brush. There was no evidence of feeding damage to the coffee leaves by the thrips, and it appears that subramanii is probably dependent on the rust fungus for its nourishment.